EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH DI KOTA DENPASAR PADA MASA PANDEMI COVID-19 - Dyah Putri Agustin; Hwihanus Hwihanus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The existence of the Covid-19 pandemic has caused the majority of small and medium enterprises to go out of business, so a business or strategy is needed to overcome these problems. . This research examines and analyzes the factors that influence the effectiveness of accounting information systems for small and medium enterprises in Denpasar City during the COVID-19 pandemic. The research sample of 91 respondents was taken by one of the probability sampling techniques, namely proportionate stratified random sampling. The analysis technique used is multiple linear regression analysis. The results of the analysis show that information technology sophistication and knowledge of accounting managers have a positive effect on the effectiveness of accounting information systems. Meanwhile, management participation and technical ability of users have a negative effect on the effectiveness of accounting information systems.